Rediscovery and systematics of the rarely encountered Blue-bellied kukri snake (Oligodon melaneus Wall, 1909) from Assam, India - Das, Abhijit; Gower, David J.; Narayanan, Surya; Pal, Saunak; Boruah, Bitupan; Magar, Sanjay; Das, Sanjib; Moulick, Soumabrata; Deepak, V. (Zootaxa, 2022)
We report the rediscovery of Oligodon melaneus 112 years after its original description and document the third, and only non-type, specimen for the species. The new specimen was found 267 km east of the type locality (Tindharia, West Bengal state) from Assam state, India. We designate a lectotype for the species, and provide an extended description of a freshly collected male specimen. Phylogenetic analyses of 16s and cytb mitochondrial genes provide support for O. melaneus being closely related to the widespread South Asian endemic O. arnensis.